Nano‐Au Anchored in Organic Base Group‐Grafted Silica Aerogel: A Durable and Robust Catalysts for Green Oxidative Esterification of Furfural. Issue 18 (29th August 2022) - Song, Fan; Cen, Shuangshuang; Wan, Cong; Wang, Lijun
Abstract: Inorganic metal (hydro)oxide supports with appropriate basicity or acid‐base properties can promote oxidative esterification of furfural over Au‐based catalysts, however, they suffer the problems of easy inactivation induced by the leaching of the components in this water‐producing reaction and the shield of catalytic sites by product adsorption. In this work, we report efficient and stable oxidative esterification of furfural over Au nanoparticles anchored in aminopropyl‐grafted silica aerogel. The support is insoluble and possesses no strong Lewis acid sites to adsorb oxygen‐containing products or intermediates, reducing the probability of catalyst deactivation induced by adsorption. In 7 cycles of reactions, the catalyst maintained the initial activity without any treatments, the yields of alkyl furoate kept above 98 %, and no agglomeration and leaching of Au occurred. Moreover, the roles of Au, alkyl chain, −NH2 group and Au‐activated O species in reactions were clarified, and accordingly, a possible catalytic mechanism involving oxidative dehydrogenation was given. Abstract : This work presented a stable and high‐efficient synergistic catalytic system based on Au nanoparticle anchored in organic base group‐grafted silica aerogel for oxidative esterification of furfural with H2 O as a by‐product, which has excellent resistance to deactivation induced by product adsorption and leaching of the components, and can almost completely convert furfural to alkyl furoate in 7 cycles.